How Servicescape And Cold-Chain Quality Affecting Procurement Behaviour: Evidence Of Mixue Indonesia - Mohammad Annas; Humairoh Humairoh; Arief Iswariyadi (Cita Konsultindo Research Center, 2023)
The objectives of the research was to uncover how the service-scape, the quality of the products, as well as the server and the price gave significant impact to procurement behavior in particular from the perspective of youth generation, which lead to youth satisfaction and end up with their loyalty towards both particular brands and products. Data collecting and observations had been done to obtain primary data resource through questionnaire and producing 317 feedbacks from those who categorized as youth generation and got sufficient understanding related to ice cream-based products. The result showed that the way operator organizing its cold-chain and maintaining the quality of the product with the right price gave significant impact to procurement behavior related to the designated products. These circumstances allowed further research to expand the variety of the products as well as the research variables to be more exposed and observed to gain coherent results.